Giordano Bruno e la civiltà europea: La lettura di Fulvio Papi (Materiali di Estetica. Terza serie, 2023)
According to Fulvio Papi, Giordano Bruno defends European culture by countering the “myth of the noble savage”, fuelled, in the modern age, by the discovery of America and supported, among other things, in Montaigne’s reflections on cannibals. However, Bruno’s is a “moderate Eurocentrism” which not only condemns the violence of the conquistadores, but is also based on a primitive idea of progress: all beings, in fact, are equal from an ontological point of view, since they are born through spontaneous generation, but only human beings, even the savages of the New World, can and must, thanks to manual industriousness, move from nature to civilization, of which European one is the model, however improvable. It is therefore in metaphysics and in the relationship between matter and form that, for Papi, the reasons for Bruno’s conception of European civilization must be sought.
Keywords: Giordano Bruno; Fulvio Papi; Europe; Spontaneous generation; Civilization